Modulation of the Suppressor of fused protein regulates the Hedgehog signaling pathway in Drosophila embryo and imaginal discs. - Dussillol-Godar, F.; Brissard-Zahraoui, J.; Limbourg-Bouchon, B.; Boucher, D.; Fouix, S.; Lamour-Isnard, C.; Plessis, A.; Busson, D. (Developmental Biology, 2006)
The Suppressor of fused (Su(fu)) protein is known to be a negative regulator of Hedgehog (Hh) signal transduction in Drosophila imaginal discs and embryonic development. It is antagonized by the kinase Fused (Fu) since Su(fu) null mutations fully suppress the lack of Fu kinase activity. In this study, we overexpressed the Su(fu) gene in imaginal discs and observed opposing effects depending on the position of the cells, namely a repression of Hh target genes in cells receiving Hh and their ectopic expression in cells not receiving Hh. These effects were all enhanced in a fu mutant context and were suppressed by cubitus interruptus (Ci) overexpression. We also show that the Su(fu) protein is poly-phosphorylated during embryonic development and these phosphorylation events are altered in fu mutants. This study thus reveals an unexpected role for Su(fu) as an activator of Hh target gene expression in absence of Hh signal. Both negative and positive roles of Su(fu) are antagonized by Fused. Based on these results, we propose a model in which Su(fu) protein levels and isoforms are crucial for the modulation of the different Ci states that control Hh target gene expression.